Organising challenges in the era of financialisation: The case of videogame workers. (1st January 2021) - Legault, Marie-Josée; Weststar, Johanna
Abstract : A long-term study of videogame developers reveals that they face challenging working conditions and wish for unionisation, although they remain mostly non-unionised. In the broad corpus of literature on propensity to unionise, scholars often offer different explanations of feeble propensity among precarious workers in low-skilled jobs, on the one hand, and those in knowledge work, on the other. We contend that this neglects a larger shared context of increasing financialisation of organisations that has a deterrent effect on intentions to unionise. The effect of financialisation on workers' representation of interests is less studied than the process of financialisation itself and its effect on worsening working conditions. Yet financial stakeholders are now important labour relations actors even while not formally present in the system. We draw on literature on propensity to unionise and new actors in labour relations to include the effect of financialisation and challenge the dichotomous explanation of propensity to unionise that opposes low-skilled jobs to knowledge work.